1997
DOI: 10.2307/1369936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Exxon Valdez Oil Spill on Birds: Comparisons of Pre- and Post-Spill Surveys in Prince William Sound, Alaska

Abstract: We used data from pre-and post-spill surveys to assess the effects of the Exxon Valdez oil spill on the abundance and distribution of birds in Prince William Sound, Alaska. We conducted post-spill surveys during midsummer (1989-1991) in 10 bays that had been surveyed prior to the spill (1984-1985) and that had experienced different levels of initial oiling from the spill (unoiled to heavily oiled). We evaluated whether there were changes in overall abundance across all bays between the pre-spill and post-spill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Also, although Murphy et al (1997) had high power for detecting a 50% postspill population decline, they did not report power for detecting smaller but biologically meaningful reductions (e.g. 10%).…”
Section: Injury and Recovery Statusmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, although Murphy et al (1997) had high power for detecting a 50% postspill population decline, they did not report power for detecting smaller but biologically meaningful reductions (e.g. 10%).…”
Section: Injury and Recovery Statusmentioning
confidence: 93%
“…Because most harlequin ducks wintering in PWS breed elsewhere, results of pre-and postspill compar- Murphy et al (1997) have limited relevance for understanding dynamics of wintering populations, which we consider to be the core, demographically distinct population segments. Also, although Murphy et al (1997) had high power for detecting a 50% postspill population decline, they did not report power for detecting smaller but biologically meaningful reductions (e.g.…”
Section: Injury and Recovery Statusmentioning
confidence: 99%
“…Oil spills can negatively influence the physiology, inmunology, and development of some organisms (Duffy et al 1994;Briggs et al 1997;Dyrynda et al 2000;Heintz et al 2000;Downs et al 2002;Rotterman and Monnett 2002), but their most evident effect is usually an important decrease or disappearance of populations of marine fauna and flora within the affected area (e.g., Frost et al 1999). The effects of crude oil on the organisms and the time needed for the recovery of ecosystems and populations are different among species, and are subject to controversy (Wiens et al 1996;Murphy et al 1997;Lance et al 2001;Esler et al 2002, Peterson et al 2003 Although the spills with the highest recognized ecological impacts were usually those in which the greatest volume of oil was spilled in the sea, a small quantity of oil spilled in pristine places can also negatively affect endangered species, as it has been reported from the Galapagos Islands after the sinking of Jessica (Wikelski et al 2002). Linked to the damage caused to the environment are the high costs to fisheries, related industries, and tourism in the affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of pre-and post-spill abundances of birds in Prince William Sound indicated that three of eleven taxa evaluated had declined significantly from numbers recorded four-five years before the spill (Murphy et al 1997) 7. 7 Fish Oil spills that occur during fish spawning or when larval concentrations are high can cause egg and larval mortality, as those are both sensitive and immobile.…”
Section: Marine Mammalsmentioning
confidence: 99%